Designing an interactive multimedia model: case study for learning german language / Sopiah Ishak - Ishak, Sopiah (2004)
Multimedia assisted learning courseware has been widely used in the field of education. It has been proven that the usage of multimedia courseware in learning foreign language does improve student's achievement. However, most course materials developed are inclined to show the sophistication of the multimedia only, rather than analysing the best method of conveying the content of the courseware. The process in building a courseware has been identified through implementing the development stages of the model. The valuable outcome is the knowledge gained in the process of building the courseware itself. In the context of multimedia development, rapid prototyping seems to be more applicable because more than one kind of communication media is involved. This includes text, graphics, sound, and video. This research is to see the process involved in the development of a particular courseware for the learning of a foreign language. The instructional system design (lSD) for the development of an interactive multimedia and the use of interactive multimedia element together with the principles of its usage are being discussed. Method for learning language is also incorporated. This method comprises concept of approach, design, and technique. This courseware is developed based on the Audiolingual and Suggestopedia method whereby the use of dialogue, quiz-drill, and game are being used in conveying the subject content together with the use of the multimedia elements. The rapid prototyping model has been chosen as the method for developing the interactive multimedia (IMM) for learning German - Malay language. Learning German (target language) for the beginner is used as the courseware content in the study. The courseware that has been developed is then evaluated based on students' perceptions. This survey was conducted on 100 students who have taken the German course for the beginners (BGM 401) at Universiti Teknologi MARA (UiTM). The three main parts evaluated are in terms of presentation, content and activities namely quiz and game. Generally, the results of the test indicated that students have a positive feedback towards this courseware.